Effects of classroom "flipping" on content mastery and student confidence in an introductory physical geology course. Issue 3 (3rd July 2019) - Jones, Jason P.; McConnell, David A.; Wiggen, Jennifer L.; Bedward, John
Abstract: Incorporating active learning strategies into introductory STEM courses has been shown to improve student outcomes, however, these activities take class time to execute. The question of how to implement these effective strategies without sacrificing a significant volume of content coverage has led to the development of a "flipped" model of instruction. This flipped model requires students to take responsibility for learning some basic concepts prior to attending class so the instructor can use newly freed class time to incorporate active learning activities. This study investigated the impact of implementing a partially flipped class format on student exam performance and confidence across four semesters of a large-enrollment physical geology course. Basic geology content was presented as pre-class homework assignments using short instructional videos ( Geoscience Videos ) that were created following empirically-derived methods of effective multimedia design. The videos facilitated an increase in the proportion of content that could be communicated outside of class and allowed for an augmentation of in-class activities on more complex geology concepts. We compared student performance and confidence across semesters and found; (a) students were able to learn the basic content as effectively as they had when it was presented in class; (b) students improved their performance on some content during summative exams; and, (c) student confidence significantly varied on some topics as a result of the course alterations. As a result, we posit that the flipped model can provide valuable opportunities to increase student learning as long as students are supported via out-of-class homework and feedback on their level of understanding regarding topics they are learning prior to attending course meetings.